Trump’s Discourse on Iran Nuclear Deal: A Critical Study - Ali Abdulhameed Faris Al-asadi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The current study, which was conducted in line with the conventions of Critical Discourse Analysis, attempts to bring forth the underlying concepts, concerning the social activities of the U. S. withdrawal from Iran nuclear deal in the discourse of the American president Donald Trump (2017). The study was centered on discussing how power is established and re-established in the discourse under investigation; in addition, Trump’s identity and ideology were also foci of the discussion of this study. The data sampling of this study was selected from “Trump’s speech on Iran Nuclear Deal” delivered on the 8th of May, 2018. To realize the objectives of the study to fruition, three theoretical insights were advocated: Fairclough’s (1989) “Relational Values”; Van Dijk’s (1990) “Discourse, Power, and Access”, and van Dijk’s (2014) “Socio-cognitive Approach to CDA”. The study came up with certain conclusions: I. there was interconnectedness between Trump’s narcissism and his utilization of personal pronouns, II. personal pronouns were manipulated in the discourse, under investigation, as a means of shaping and reshaping social structures, III. some of the lexical items utilized in the given discourse were potential enough to display Trump’s attitude of hostility and aggressiveness towards Iran, an attitude that was structured by his socio-cognitive background on the Iranian politics after 1979, and IV. conditional constructions were employed by Trump to configure hypothetical realities on the Iranian nuclear deal and the Iranian political system.